Pengembangan Bahan Ajar Berbasis Blended Learning pada Mata Kuliah Ilmu Pendidikan Prodi Pendidikan Agama Islam - Zainatur Rahmah; Jasiah Jasiah; Fimeir Liadi (ISLAMIKA, 2023)
The background of this research is that the limitations of teaching materials in the subject of Education tend to be carried out manually. The formulation of the problem in this study is that is it feasible for blended Learning-based teaching materials in the Educational Sciences course to be used in the PAI Study Program. This study aims to produce products in the form of Blended Learning-based teaching materials in PAI Education Study Program subjects. This research uses development research methods, carried out through ten stages using the Dick and Carey model. To find out the feasibility of the product being developed, quantitative data is needed in the form of response scores about product quality through a questionnaire validated by media experts and material experts and student responses. The results of the study showed that teaching materials based on blended learning through the Macromedia Flash 8 program in the subject of Education in the first semester of the PAI study program on the components of education had a “very good” feasibility category which was based on the percentage gain using the Likert scale. The results of validation and trials include (1) the validation of the material expert said that the final percentage obtained from the material and linguistic aspects is 89.09% with very good criteria, (2) Validation of media experts stated that the final percentage obtained from material and display aspects was 100,00% with very good criteria, (3) Individual trials stated that the final percentage obtained from material and display aspects is 78.95% with good criteria (4) Small group trials state that the final percentage obtained is 90,67% with very good criteria (5) and field trials state that the final percentage obtained is 91,40% with very good criteria.single paragraph of abstract, about 150-250 words without indentation of the first line with 1 spaces and 11-point. We strongly encourage authors to use the following style of structured abstracts, but without heading: (1) Background: place the gap analysis of this study (about 1-2 sentences) and highlight the purposes of the study; (2) Methods: briefly describe the main methods applied, including samples/participants, instruments, collecting data technique, and analyzing data technique; (3) Results: summarizing the article’s main findings, should be in line with the purposes of the study; (4) Conclusion. The abstract should be an objective representation of the article. It must not contain results that are not presented and substantiated in the main text and should not exaggerate the main conclusions.